Strategic reference points, risk and strategic choices in small and medium-sized enterprises - García-Pérez, Ana María; Yanes-Estévez, Vanessa; Oreja-Rodríguez, Juan Ramón (Journal of Business Economics and Management, 2014)
This article presents a realistic view of the strategic process in small and medium-sized enterprises (SMEs). The study integrates prospect theory and strategic reference point theory: strategic choices depend on how the decision maker perceives the situation in relation to the reference and the risk being taken. Applying Rasch models to a sample of firms in the Canary Islands (Spain), the results show that SMEs that are more influenced by external references take higher risks. These enterprises differ in their strategic choices from those that do not focus on external references in the greater importance they attach to market diversification. This study is pioneer in considering the internal and external dimension of references that SME managers have in mind and linking them, via prospect theory (Kahneman, Tversky 1979), to the risk they take in their strategic choices. It also has the added value of applying Rasch Measurement Theory.For managers, the study of the SRPs shows a large number of enterprises with a more internal than external view. Thus, the need for rethinking their SRPs and for designing a greater market orientation of firms in the service sector is worth highlighting.There are also important implications for the public administration and institutions. They should emphasize the promotion of cooperation among enterprises to increase their external orientation and then, the importance of external SRPs. Training, financial and organizational support could be some of the strategies that ought to be implemented.First published online:  02 Oct 2013